The Contribution of the Safavid Dynasty to the Formation of the Islamic Family Law System: Institutionalization of Ja’fari Jurisprudence in Marriage, Divorce, and Inheritance Regulations in Iran - Lidia Sandy Kartika; Athia Nur Kamilah; Falih Akmal Wicaksono (Universitas Darunnajah Jakarta, Indonesia, 2026)
This study examines the contribution of the Safavid dynasty (1501–1736) to the formation of the Islamic family law system in Iran, with a particular focus on the institutionalization of Ja'fari jurisprudence in regulating marriage, divorce, and inheritance. Using a historical-juridical approach with qualitative library research methods, the study traces how the Safavid political transformation from a Sufi order (tar?qah) into a Twelver Shi'a state provided the structural foundation for codifying family law norms derived from the Ja'fari school of thought. The findings reveal that the Safavid era introduced significant legal innovations in three key domains: the formalization of permanent (nik??) and temporary (mut'ah) marriage contracts under state-administered shar?'ah courts; the systematization of divorce procedures including ?al?q, khul', and judicial dissolution; and the implementation of inheritance distribution based on far?'i? principles. The study concludes that the Safavid legacy in family law continues to shape Iran's modern legal framework. This study contributes to the existing body of knowledge by providing an integrative analysis that bridges the gap between Safavid political historiography and Islamic legal studies, specifically by disaggregating the institutional mechanisms such as the role of the ?adr, the appointment of Shi'a q???s, and the scholarly migration from Jabal '?mil through which Ja'fari family law norms were systematically codified and enforced, an area that has been largely overlooked in prior scholarship which tends to treat the Safavid legal system as a monolithic entity without examining its specific innovations in the domains of marriage, divorce, and inheritance regulation.